Pengaruh Latihan Small Side Games Terhadap Keterampilan Bermain Sepakbola - Raden Dadan Pra Rudiana; Arif Fajar Prasetiyo (Politeknik Kampar, 2023)
The aim of this research is to find out the effect of training in side games on soccer playing skills. This research method uses an experimental method with a research population of 20 students. This research uses a total sampling technique, where the entire population is the research sample, so the number of samples in this research is 20 students. The instrument used in this research is the GPAI football instrument. From the results of research that has been carried out, there is a significant influence of small side games training on soccer playing skills.